2021
DOI: 10.5398/tasj.2021.44.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Laying Alabio Duck and its Eggs Quality under Exposure of Different Intensity and Color of LED Light

Abstract: The purpose of this study was to analyze the different combinations of intensity and color of LED monochrome lamps for optimal productivity, as well as the internal and external quality of Alabio duck eggs. The study was carried out for 4 weeks period of raising which was devided in 2 stages. In the first stage, it was used a completely randomized factorial design of 4 light colors x 3 light intensities with 4 replications with 5 ducks of each replicate, totaling 240 laying Alabio ducks. The light color was 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
1
2
Order By: Relevance
“…According to Yoselewitz and Balnave [ 25 ] and Espinar et al [ 26 ], drinking water with high salinity reduced the shell thickness due to decreased activity of the carbonic anhydrase enzyme in the formation of shells. The shell thickness in the study was in the normal category (313–320 µm) and relatively similar to a study reported by Rostini et al [ 4 ] (309–337 µm). These findings are supported by Alam et al [ 15 ], who noted that poultry that lacks salt gland secretions, such as ruminants, can be affected by high salt levels in the environment.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…According to Yoselewitz and Balnave [ 25 ] and Espinar et al [ 26 ], drinking water with high salinity reduced the shell thickness due to decreased activity of the carbonic anhydrase enzyme in the formation of shells. The shell thickness in the study was in the normal category (313–320 µm) and relatively similar to a study reported by Rostini et al [ 4 ] (309–337 µm). These findings are supported by Alam et al [ 15 ], who noted that poultry that lacks salt gland secretions, such as ruminants, can be affected by high salt levels in the environment.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, the provision of ingredients could reduce pathogenic bacteria to improve the productive performance of laying ducks by optimizing the feed metabolism and thus supporting the availability of required nutrients for egg production [ 22 ]. Egg production obtained in this study was substantially lower than that in the experiment carried out by Rostini et al [ 4 ], who reported that the egg production of Alabio ducks ranged between 47% and 81%. The low egg production occurred as the ducks were still in their initial production period (2–3 months).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…However, selection and breeding efforts for Alabio ducks are currently lacking. A few unpublished studies suspected that Alabio ducks experienced a decline in genetic quality, both in production quantity and quality, due to increased inbreeding caused by mating between close relatives [ 4 ]. On the other hand, a crucial issue that is currently happening is the threat to the purity of the Alabio duck by the introduction of various duck breeds from different regions, such as Mojosari ducks, Tegal ducks, and Pekin ducks, and also the occurrence of crossbreeding without strict and directed management.…”
Section: Introductionmentioning
confidence: 99%